THE INFLUENCE OF HUMAN CAPITAL, SOCIAL CAPITAL AND FINANCIAL CAPITAL TO BUSINESS RESILIENCE OF SME’S IN MANADO - Fernanda Tambayong; Joy Elly Tulung; Merinda H. Ch. Pandowo (Universitas Sam Ratulangi, 2023)
Business Resilience is one important characteristic that surely warrant the survival from all business players in the market, especially when competing in the pandemic-based situation. Human Capital, Social Capital and Financial Capital are three essential factors that are significant in establishing, maintaining and increasing Business Resilience from any company or business unit. This study aims to figure out the influence of Human Capital, Social Capital and Financial Capital toward Business Resilience from UMKM units that are competing in the Manado City. Overall population in this research is UMKM units that are competing in the Manado City and the chosen sample is 31 respondents. Data analysis uses multiple linear regressions analysis method. This research result proves that Human Capital, Social Capital and Financial Capital simultaneously have positive and significant impact and partially only Human Capital and Social Capital have positive and significant influence Business Resilience from those business units. Owners and management from each one of them have to preserve and boost Human Capital, Social Capital and Financial Capital in every business unit and deliberate other factors that influence the Business Resilience from UMKM units that are competing in the Manado City. Keywords: human capital, social capital, financial capital, business resilience